The Implication Of Bureaucratic Reform Of Public Services On Citizen Trust And Satisfaction: Case Study In Department of Population and Civil Registration Merangin Regency, Jambi Province - Dimas Subekti; Ulung Pribadi (Kolaborasi : Jurnal Administrasi Publik, 2022)
This study aims to find to what extent the public services carried out by the Merangin Regency Population and Civil Registration Service give implications for trust and satisfaction to the community. This study uses a quantitative approach. This study uses SMART PLS in analyzing data. The source of this research data comes from 100 respondents from the Merangin community using a questionnaire tool via Google Form. The findings in this study are first, that procedures and accountability have a significant effect on the trust of  the citizens of Merangin. Meanwhile, regulations, organizational structure, human resources and technology do not have a significant effect on the trust of the Merangin citizent. Second, that public trust in the Department of Population and Civil Registry Service has a positive effect on citizent satisfaction with public services provided. Third, that regulations, procedures, organizational structures, human resources, technology, and accountability have more influence on citizens than on the government. Meanwhile, citizens' trust in the government has a strong influence on citizens' satisfaction with public services.